The nocebo effect: a clinical challenge in the era of biosimilars. (2nd September 2018) - Pouillon, Lieven; Socha, Marie; Demore, Beatrice; Thilly, Nathalie; Abitbol, Vered; Danese, Silvio; Peyrin-Biroulet, Laurent
ABSTRACT: Introduction : The nocebo effect is defined as a negative effect of a pharmacological or non-pharmacological medical treatment that is induced by patients' expectations, and that is unrelated to the physiological action of the treatment. The nocebo effect is an important clinical challenge in the current era of biosimilars. Areas covered : This review aims to answer five key questions about the nocebo effect, namely to reveal its definition, pathophysiology, clinical relevance, contributing factors, and management. Expert commentary : The nocebo effect lowers patients' quality of life and negatively affects treatment adherence rates in biosimilar-treated patients. It may negatively impact on the cost-savings of biosimilars. Health-care providers in charge of biosimilar-treated patients need to be aware of the nocebo effect and adopt strategies to minimize it. They have to be well-informed and confident about the existing evidence about biosimilars. A good patient–physician relationship will improve patients' acceptance of biosimilars, and limits the risk of inappropriate negative bias and the nocebo effect.